Corrosion behavior of silver-coated conductive yarn - Park, Jihye; Park, Sun Hwa; Jeong, Soo-Hwan; Lee, Jung-Yong; Song, Jae Yong (Frontiers in Chemistry, 2023)
The corrosion mechanism and kinetics of the silver-coated conductive yarn (SCCY) used for wearable electronics were investigated under a NaCl solution, a main component of sweat. The corrosion occurs according to the mechanism in which silver reacts with chlorine ions to partly form sliver chloride on the surface of the SCCY and then the local silver chloride is detached into the electrolyte, leading to the electrical disconnect of the silver coating. Thus, the electrical conductance of the SCCY goes to zero after 2.7 h. The radial part-coating of gold, which is continuously electrodeposited in the longitudinal direction on the SCCY but is partly electrodeposited in the radial direction, extends the electrical conducting lifetime up to 192 h, despite the corrosion rate increasing from 129 to 196 mpy (mils per year). Results show that the gold partly-coating on the SCCY provides a current path for electrical conduction along the longitudinal direction until all the silver underneath the gold coating is detached from the SCCY strands, which creates the electrical disconnect. Based on the corrosion behavior, i.e., local oxidation and detachment of silver from the SCCY, the gold part-coating is more cost effective than the gold full-coating electrodeposited on the entire surface for electrically conducting SCCY.